2015
DOI: 10.1161/strokeaha.114.007445
|View full text |Cite
|
Sign up to set email alerts
|

Blood–Brain Barrier KCa3.1 Channels

Abstract: Background and Purpose KCa3.1, a calcium-activated potassium channel, regulates ion and fluid secretion in the lung and gastrointestinal tract. It is also expressed on vascular endothelium where it participates in blood pressure regulation. However, the expression and physiological role of KCa3.1 in blood-brain barrier (BBB) endothelium has not been investigated. BBB endothelial cells transport Na+ and Cl− from the blood into the brain transcellularly through the cooperation of multiple co-transporters, exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 64 publications
1
39
0
1
Order By: Relevance
“…In addition to activated microglia and macrophages, KCa3.1 is also expressed on blood-brain barrier endothelial cells, where it helps drive transcellular Na þ transport by the Na-K-Cl cotransporter (NKCC) and the Na/H exchanger (NHE) in the first few hours after ischemic stroke when the blood-brain barrier is still intact. 33 Using magnetic resonance spectroscopy and Na þ imaging, we recently demonstrated that TRAM-34 treatment started immediately before induction of permanent MCAO in rats significantly delayed edema formation and brain Na þ uptake. 33 These edema reducing effects of KCa3.1 inhibition are very likely responsible for the better outcomes of the KCa3.1 mice early after MCAO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to activated microglia and macrophages, KCa3.1 is also expressed on blood-brain barrier endothelial cells, where it helps drive transcellular Na þ transport by the Na-K-Cl cotransporter (NKCC) and the Na/H exchanger (NHE) in the first few hours after ischemic stroke when the blood-brain barrier is still intact. 33 Using magnetic resonance spectroscopy and Na þ imaging, we recently demonstrated that TRAM-34 treatment started immediately before induction of permanent MCAO in rats significantly delayed edema formation and brain Na þ uptake. 33 These edema reducing effects of KCa3.1 inhibition are very likely responsible for the better outcomes of the KCa3.1 mice early after MCAO.…”
Section: Discussionmentioning
confidence: 99%
“…33 Using magnetic resonance spectroscopy and Na þ imaging, we recently demonstrated that TRAM-34 treatment started immediately before induction of permanent MCAO in rats significantly delayed edema formation and brain Na þ uptake. 33 These edema reducing effects of KCa3.1 inhibition are very likely responsible for the better outcomes of the KCa3.1 mice early after MCAO. It could of course also be argued that TRAM-34 was not optimally dosed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There are no reports of K + , Cl − cotransporters being present or active at the blood–brain barrier but also no reports of a careful search. By contrast many K + channels have been characterized in cultured brain microvascular endothelial cells using patch clamp experiments [240, 332, 338348]. In acutely dissociated rat brain endothelial cells mRNA is present and there are functional signatures for channels containing Kv1.3, Kir2.1 and Kir2.2 [332].…”
Section: Ion and Fluid Transport At The Blood–brain Barriermentioning
confidence: 99%
“…A disturbance of energy metabolism can contribute to the reduction of the ADC via cell swelling (23). Cerebral edemas likely formed in the presence of an intact blood-brain barrier (BBB) while transendothelial secretion of Na + , Cl − and water into the brain was greatly increased (24).…”
Section: Meanmentioning
confidence: 99%